REVOLUSI INDUSTRI 4.0: INTERNET OF THINGS, IMPLEMENTASI PADA BERBAGAI SEKTOR BERBASIS TEKNOLOGI INFORMASI (BAGIAN 1) - Mantik, Hari (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2022)
Internet of Things (IOT) is a concept where an entity is implanted with state-of-art technology such as sensors, systems, and applications with the aim of communicating with each other, controlling, connecting and exchanging data through the internet. This integration is part of the business or work that is currently required. Work is not only focused on one or two things, but is connected across functions, across sectors and regions on an ongoing basis. This paper explores one part of the industrial revolution 4.0 (Internet of Things) which plays a very important role in connecting all systems across everything continuously.Â keywords: Internet of Things, revolusi industri